Impact of migration on the vulnerability of poverty: A case study on the agricultural households in West Java Province, Indonesia - Gilang Wirakusuma; Imade Yoga Prasada; Ilmas Abdurofi (Universiti Malaysia Sarawak, 2023)
Rural area in Indonesia relies heavily on the activity in agricultural sectors, while the source of income from the rural households is considerably obtained by the effort of cultivating the agricultural products or commodities. Nevertheless, several problems arise from the issue among agricultural households, as one of them is migration. Indeed, most migrants come to rural areas due to livelihood and poverty alleviation motives. Hence, the objectives of the study are to identify the determinants for agricultural households involving family members in rural-urban migration and measure the impact of migration on vulnerability to poverty. The study focuses on observing primary data with a face-to-face interview of 400 agricultural households in the area of West Java, Indonesia as a sample size. Then, the analysis uses the model of Propensity Score Matching (PSM), which is estimated by using the Probit Model. The empirical evidence from a Probit model indicates that the variables of the household head’s age, education level, household size, house ownership and per capita expenditure significantly determines the propensity of agricultural households to be involved in migration movement. Meanwhile, migration activity has a positive impact on decreasing vulnerability to poverty by the agricultural households in West Java, Indonesia.